2017
DOI: 10.1016/j.burns.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different duration exercise programs in children with severe burns

Abstract: Introduction Burns lead to persistent and detrimental muscle breakdown and weakness. Standard treatment at our institution includes a voluntary 12-week rehabilitative exercise program to limit and reverse the effects of increased muscle catabolism. In the present work, we investigated if different durations of exercise, 6 or 12 weeks, produce comparable improvements in muscle strength, body composition, and cardiopulmonary fitness. Methods We prospectively enrolled and randomized patients with ≥30% total bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…41 However, our previous work has found that burned children do improve aerobic and strength capacities. [14][15][16][17][18][19][20][21] Further, our results have consistently shown that the burned men group responded to a greater degree than our burned children. It is not clear why there are differences, but we do show (in Figure 3 and Table 2) that the relative relationship between heart rate and oxygen uptake differs between groups.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…41 However, our previous work has found that burned children do improve aerobic and strength capacities. [14][15][16][17][18][19][20][21] Further, our results have consistently shown that the burned men group responded to a greater degree than our burned children. It is not clear why there are differences, but we do show (in Figure 3 and Table 2) that the relative relationship between heart rate and oxygen uptake differs between groups.…”
Section: Discussionsupporting
confidence: 76%
“…Nonburned normative data for peak torque were obtained from our database and our previous published studies. [14][15][16][17][18][19][20] Data were analyzed and figures generated using GraphPad Prism (Version 6.0, La Jolla, CA, USA), with significance set at P < .05. All data are reported as mean ± SD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement seen in both groups after exercise supports the utility of RET in severely burned individuals. Although we did not have a non-exercising group to compare the data and account for the effect of time as patients convalesce, previous randomized studies suggest that improvements in muscle mass and strength in the first few months post burn injury are significantly augmented in patients who participate in an exercise program compared to those who do not (9, 13, 39).…”
Section: Discussionmentioning
confidence: 99%